Existe uma experiência estética do usuário nosdiscursos da arquitetura contemporânea?: aproximações a partir das categorias críticas dePeter Eisenman e Bernard Tschumi - Silvia de Alencar Renno (2006)
From analysis of some texts by two great contemporary architects Peter Eisenman e Bernard Tschumi the purpose is to investigate whether the discourses about contemporary architecture contemplate the users aesthetic experience and to what extent. Since Benjamins diagnosis of cultural situation carried out in the 1930s denounces a poverty state of experience, studying the current situation inarchitectural context has become intriguing, which goes through the relationship between body an architecture, the characterization of a user participating in an experience, as well as the variations of aesthetic experience concepts. Peter Eisenman, with his initial emphasis on the investigation of a possible autonomy in architecture, focuses his discussions more on the formal question than on spatial, setting aside from the process of architectural formation any external factors,including the user, to whom a role of reader is attributed. However, the architect alters his position in dealing with the concepts of looking back and fold in his last text herein analyzed, which made him regard as fundamental the question of the users experience. The same is seen in Bernard Tschumis discourses, which are strongly marked by the belief in the space/event duality. For him architecture is not only formal conception but also includes the activities which occur in space and theexperience of the movement of bodies in its interior, which shows clearly Tschumis defense for a relationship between subject and object as indispensable for the architectures formation.